Metody leczenia chorób wśród ludu polskiego w XIX wieku. Próba bilansu - Domańska, Aneta (Zeszyty Wiejskie, 2016)
Knowledge of folk medicine is still fragmented and not fully tested. Folk medicine are rural home remedies, which are based mainly on raw materials derived from the plant world, ergo of herbs, shrubs, bushes and trees, and vines, lichens and fungi. Wild plants and plants cultivated for this end. Folk medicine also includes prayers and songs to the saints responsible for the care and treatment of diseases and plagues. The image of this kind of treatment in public opinion, and also in many other backgrounds, is generally tight and shallow, distorted and heavily tendentious, which makes it false. Many of the ways to maintain health were written in contemporary literature, periodicals as well as in monographic publications worked out by ethnographers, sociologists and a very few doctors. Some of the contemporary knowledge has survived and is used in herbalism today.